2021
DOI: 10.1016/j.jadohealth.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Youths' Perspectives on Telehealth for Delivery of Gender-Affirming Care

Abstract: Purpose We aimed to examine transgender youths' interest in receiving gender-affirming care via telemedicine or through primary care with telehealth support. Methods We surveyed 12- to 26-year-old transgender youth receiving care in a multidisciplinary gender clinic. Descriptive statistics and bivariate analyses were used to assess relationships between demographic and gender-related characteristics and interest in receiving care via telemedicine. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…4 Another study of transgender youth by Sequeira et al found that almost half of the 204 youth surveyed expressed an interest in receiving gender-affirming care through telehealth, and youth with lower perceived parental support were more likely to express an interest in telehealth for gender-affirming care. 8 Baseline access to gender-affirming care services in the United States Heartland and South is already significantly limited, with many states and regions, including rural areas, having limited or no access to gender-affirming care providers at all. 6 A growing body of research suggests that long-term deprivation of adequate transgender care may increase existing allostatic load (i.e., stress), and poor mental health outcomes, including depression, nonsuicidal self-injury, and suicidal ideation and behavior, which can ultimately result in a decreased life expectancy of transgender people.…”
Section: Introductionmentioning
confidence: 99%
“…4 Another study of transgender youth by Sequeira et al found that almost half of the 204 youth surveyed expressed an interest in receiving gender-affirming care through telehealth, and youth with lower perceived parental support were more likely to express an interest in telehealth for gender-affirming care. 8 Baseline access to gender-affirming care services in the United States Heartland and South is already significantly limited, with many states and regions, including rural areas, having limited or no access to gender-affirming care providers at all. 6 A growing body of research suggests that long-term deprivation of adequate transgender care may increase existing allostatic load (i.e., stress), and poor mental health outcomes, including depression, nonsuicidal self-injury, and suicidal ideation and behavior, which can ultimately result in a decreased life expectancy of transgender people.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the impact of gender-related distress specific to voice or appearance may become most pronounced when TGD individuals seek to establish care with a new health service psychologist. In such instances, increased preoccupation with one's voice and appearance, fear of invalidation, rejection, or misgendering from an unfamiliar provider may intensify gender-related distress (Sequeira et al, 2021 ). In the vignette, Sam intentionally left their gender identity and pronouns blank on the intake packet out of concern of the new health service psychologist not understanding or rejecting them if they disclosed.…”
Section: Telepsychology Services For Transgender and Gender Diverse Individualsmentioning
confidence: 99%
“…Next, verbally confirm the patient's affirmed name and pronouns listed on the intake packet. Providing Sam with the intake packet and verbally checking back with Sam about the information on the intake packet, and the health service psychologist’s self-disclosure of pronouns, informed Sam that the health service psychologist had an awareness of gender-affirming practices (Loo et al, 2021 ; Sequeira et al, 2021 ).…”
Section: Clinical and Ethical Challengesmentioning
confidence: 99%
“…Existing literature has shown that many components of adolescent health care can be provided effectively through telehealth ( 3 5 ). In the past year, several academic institutions in the United States have also published on the challenges, opportunities, and impact of a rapid scale-up of telehealth use in Adolescent Medicine in the setting of the pandemic ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%